Analysis of ChatGPT Tool to Assess the Potential of its Utility for Academic Writing in Biomedical Domain - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
Background: ChatGPT (Generative Pre-trained Transformer) is an artificial intelligence chatbot which is designed to generate detailed text response and/or articulate answers to any query. Widespread concerns are expressed that such tools can be misused for academic writing. Hence this study was designed to test the utility and merit of ChatGPT for academic writing in biomedical sciences. Materials and Methods: five randomly selected quey topics were input into ChatGPT for a response. The ChatGPT response time, quality of the content and reliability were assessed. The ChatGPT response was transferred into a word file and the file was checked for originality using the Urkund software. Results: The response rate by ChatGPT was observed to be very quick i.e., less than 2 min to give a 300-500 words text output. Although the content of the response were systematic, precise and original, it lacked quality and depth of academic writing. Several shortcomings such as word count, referencing errors and lack of academic merit were observed. Conclusion: Despite its significant limitations, ChatGPT has enormous potential as training and upskilling resource for academic writing, which rather than replacing biological intelligence will help in refining it if used appropriately under academic mentoring.
Keywords: Universal design for learning; Artificial intelligence; Biological intelligence; Plagiarism; Academic writing